Principles of Reporting on Complex Financial Instruments in the Issuer According to IFRS - the Voice in the Discussion - Dratwińska-Kania, Beata (Studia Oeconomica Posnaniensia, 2018)
This article summarizes the principles for recognizing complex financial instruments in an issuer, where there is a need to separate the equity instrument and financial liability. There was also a critical assessment of IFRS, concerning complex financial instruments. The aim of the article is to criticize the reporting of complex financial instruments in the issuer. The research method is a critical analysis of the regulation of IFRS.